The load-bearing duct: biomimicry in structural design - Wadee, M. Ahmer; Hunt, Gary R.; Yiatros, Stylianos (My University, 2007)
The philosophical aspects of applying the principles of biomimicry are explored in a case study of structural design. Integrating structural engineering with services engineering can be regarded, to some extent, as taking principles from biological systems and applying them to large-scale conceptual design. The end-product discussed herein a so-called load-bearing duct, a functional naturally ventilated multi-storey office building that takes the applied loading efficiently both structurally and cost-effectively giving it the potential to be sustainable throughout its design life.
Keywords: Buildings, structures & design; Environment